(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Low back pain (LBP) is a common musculoskeletal disorder and a major cause of disability worldwide. The Modified Oswestry Disability Index (MODI) is a validated tool used to assess disability related to LBP.Magnetic Resonance Imaging (MRI) is widely used to evaluate degenerative changes in the lumbosacral spine;however, degenerative findings may also be present in asymptomatic individuals, leading to variability between imaging and clinical severity. Aims and Objectives: To correlate the radiological changes in low back pain by Magnetic Resonance Imaging (MRI) with clinical severity by Modified Oswestry Disability Index (MODI) in patients with low back pain. Materials and Methods: In this prospective observational study, 80 patients aged ≥18 years presenting with LBP were assessed using the Modified Oswestry Disability Index (MODI) questionnaire. Subsequently, MRI of the lumbosacral spine was performed, and degenerative changes across five lumbar intervertebral disc levels were graded and correlated with MODI scores. Results: The mean age of the study population was 46.84 ± 16.2 years with a slight female predominance. Degenerative changes were most frequent atL4/L5 and L5/S1 levels. Most patients demonstrated mild MRI degeneration (82.5%), and minimal disability was observed in 53.75%. MRI grading showed a statistically significant association with disability categories (P < 0.001) along with a strong positive correlation (Spearman’s r = 0.950). Conclusion: Higher MRI grades of lumbar degeneration were associated with greater functional disability in patients with LBP. MRI grading may aid structural assessment in appropriately selected symptomatic patients, but findings should be interpreted in conjunction with clinical evaluation.